2015
DOI: 10.1155/2015/691594
|View full text |Cite
|
Sign up to set email alerts
|

Ergosterol Alleviates Kidney Injury in Streptozotocin-Induced Diabetic Mice

Abstract: Ergosterol (ERG) has been widely used in the development of novel drugs due to its unique physiological function. However, little is known about the protective effects of ERG on diabetes. Hence, the current study was designed to evaluate the positive role of ergosterol on streptozotocin- (STZ-) induced diabetes in mice. Oral glucose tolerance test (OGTT) was carried out to assess blood glucose level. Biochemical parameters such as uric acid, creatinine, serum insulin, triglycerides (TG), and total cholesterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…However, various antidiabetic drugs and herbal administration have proven inefficacy in preventing DN and leads to further complications [12, 15]. Hence, the current study extended to elucidate renoprotective activity of antidiabetic CmNo1 (already described in previous report) [22]. The mouse model exhibited metabolic abnormalities (hypoinsulinemia, hypertriglyceridemia, and hypercholesterolemia) and renal lesions resembling DN in humans [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, various antidiabetic drugs and herbal administration have proven inefficacy in preventing DN and leads to further complications [12, 15]. Hence, the current study extended to elucidate renoprotective activity of antidiabetic CmNo1 (already described in previous report) [22]. The mouse model exhibited metabolic abnormalities (hypoinsulinemia, hypertriglyceridemia, and hypercholesterolemia) and renal lesions resembling DN in humans [31].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fruiting body extract have been reported to possess greatest hypoglycemic activity than other strains and components but owing to host specificity and rarity in nature the fruiting bodies are much expensive [20, 21]. In our previous study, antidiabetic activity of CmNo1 has already been demonstrated [22]. So, in this report, we aimed to investigate whether CmNo1 also possess renoprotective effect.…”
Section: Introductionmentioning
confidence: 99%
“…Oleic acid has been reported to counteract with the inhibitory effect of inflammatory cytokines in insulin production [62]. Ergosterol has been reported to possess significant hypoglycemic effect and counteract with diabetic pathophysiology via inhibiting NF-κB mediated inflammatory signals [63]. Stigmasterol is also known to possess hypoglycemic effect [64].…”
Section: Discussionmentioning
confidence: 99%
“… Restore PI3K/Akt signaling damaged in diabetic mice; ergosterol-related compounds induce cell apoptosis depending on a protein-promoted Akt activation. [ 177 , 178 ] Garlicin Human cellosaurus cells Suppress PI3K/Akt pathway. [ 179 ] Garlic Fructose-fed diabetic SD rats Activate PI3K/Akt in Diabetes rats.…”
Section: Dietary and Pharmacological Considerations That Influence Gsmentioning
confidence: 99%